APLIKASI PETA DIGITAL UNIVERSITAS MUHAMMADIYAH SURAKARTA - Syams Kurniawan Hidayat (Universitas Muhammadiyah Surakarta, 2011)
Nowadays, the campus map in Muhammadiyah University of Surakarta is made from paper as a conventional map. It can not helps people to find a location and its description in easier way. For example, when we want to find the location of Student Extracuricular Group (UKM), faculties, canteen and the other places, we must have a map and search it manually. This research is aimed to make a digital map aplication to help the searching of locations in Muhammadiyah University of Surakarta. It also provides the description or information of a location in detail. Every registered member can upload the data to give the description of the given location. This digital map application will help the administrator in the data editing, because it can be done in everytime and everywhere. The type of the study is qualitative research. The data collections are done with interview to Muhammadiyah University of Surakarta’s students and direct observation to the Student Extracuricular Group (UKM) locations. After gets the data, the writer processes the data with Macromedia Flash 8, PHP software and MySQL database. The trial can be done by localhost server or internet acces. This research have succeeded in making digital map application which can be accessed by Local Area Network (LAN) and internet as the advantage. It can helps the searching of a location for both internal users and external users in Muhammadiyah University of Surakarta. This application is also dynamic because it can be edited as the current appropriate condition of a location.